Calorie restriction upregulated sirtuin 1 by attenuating its ubiquitin degradation in cancer cells. (March 2014) - Han, Limin; Zhao, Ganye; Wang, Hui; Tong, Tanjun; Chen, Jun
Summary Sirtuin (SIRT) 1 is a key protein in mediating the benefits of calorie restriction (CR) in mammals. However, the molecular mechanisms underlying CR‐induced SIRT1 upregulation in mammals remain unclear. Herein we show that the elevated SIRT1 levels are not due to increased SIRT1 mRNA expression. but rather to enhanced SIRT1 protein stability as a result of reduced ubiquitin‐proteasome degradation of SIRT1 under limited nutrient conditions. Our observations have important implications for improving healthy aging in humans.